Molecular interactions at the interface: polyoxometalates of the Anderson-Evans type and lipid membranes - Pashkovskaya, Alina A.; Gumerova, Nadiia I.; Rompel, Annette; Pohl, Elena E. (Frontiers in Chemical Biology, 2024)
Polyoxometalates (POMs) are metal-oxygen clusters composed of MO6 octahedra that have attracted considerable attention due to their remarkable antiviral, antibacterial and antitumor activities. Despite their potential, the molecular mechanisms underlying their cellular toxicity remain poorly understood. This study investigates how Anderson-Evans type polyoxotungstates (POTs) and polyoxomolybdates (POMos) interact with biological membranes by examining their effects on the zeta (ζ) -potential of the lipid bilayer and the size of small unilamellar liposomes of different phospholipid compositions. POTs affected the ζ-potential of neutral (1,2-dioleoyl-sn-glycero-3-phosphocholine, DOPC) and slightly negatively charged (1,2-dioleoyl-sn-glycero-3-phosphoethanolamine; DOPC:DOPE) membranes in the order [MnW6O24] 8-˃ [Ni(OH)6W6O18] 4-˃ [TeW6O24] 6-. The addition of negatively charged cardiolipin (CL) to DOPC reduced the interaction of POTs with the membrane. An opposite effect was observed for POMos, which changed the ζ-potential of neutral and slightly negatively charged membranes in the order [Al(OH)6Mo6O18] 3-ꞏ˃[Cr(OH)6Mo6O18] 3-˃˃ [Ni(OH)6Mo6O18] 4-.The addition of POMos increased the size of the liposomes in reverse order. The binding of [Al(OH)6Mo6O18] 3-ꞏto the PE-containing phospholipid membranes and the effect of ionic strength on the interaction of [Cr(OH)6Mo6O18] 3-with DOPC:CL liposomes could be inhibited by potassium fluoride (KF). Interestingly, KF did not inhibit the interaction of other POMos with membranes as indicated by ζ-potential measurements. These results suggest that the interaction of Anderson-Evans type POMs with phospholipid membranes is influenced more by their addenda and central ions than by their total charge. By unravelling the structure-activity relationships for the different POM archetypes, we contribute to the design of biologically active POMs for therapeutic use.The family of inorganic anionic metal oxide clusters, polyoxometalates (POMs), includes numerous members with very distinct but highly adjustable structures. Due to their tuneable composition, variable structure and chemical properties, POMs have been successfully applied in various scientific fields (Guo et al., 2023). It is possible to incorporate different chemical ions into the metal-oxide framework of heteropolyoxoanions and even replace POM segments with organic ligands to form hybrid organicinorganic POMs (Blazevic et al., 2015). POMs have attracted considerable medical attention due to their antitumor, antiviral, and antibacterial activities, making them potential candidates for drug research and diagnostic applications (Bijelic et al.